Sistem Pendukung Keputusan dalam Penentuan Jurusan Berdasarkan Minat Siswa SMK Harapan Stabat Menggunakan Metode SAW - Randa Ersada; Eka Ade Putri; Febly Fauziah; Arista Widya Ningsih; Safrizal Safrizal (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2025)
For prospective students, SMK Harapan Stabat offers five main subjects with a specialization system that does not require exams. The number of students majoring in office administration has increased, and majoring procedures have shifted from conventional assessments to skills-based assessments. The current method, however, is challenging, especially for the Assistant Curriculum Director because it relies on exam results reports. To solve this problem, this research creates a web-based application that uses the simple additional reduction (SAW) method. This application is intended to help school principals determine student majors more efficiently. The implementation results show that this application was well received by the students of SMK Harapan Stabat and can help them make decisions about their major. Currently, determining majors at SMK Harapan Stabat is not ideal because prospective students tend to choose majors according to their own wishes. In addition, schools only look at test scores without considering students' interests and talents as well as other factors that influence acceptance in certain majors. Collecting data on students' aptitudes, interests, and test scores is critical to improving this process. Therefore, to carry out more accurate calculations, the Simple Additive Weighting (SAW) method is needed. Schools can use this decision support system to make better decisions about the majors their students will take. Therefore, the choice of major is expected to be more appropriate to students' abilities and interests to support their future success.